Consciousness: A rapidly moving Scientific Discipline? (International Journal of Emerging Trends in Science and Technology, 2017)
Is consciousness a discipline of Philosophy/Theology or Science? Since time immemorial, consciousnesshas baffled us, bewildered us and sometimes even mystified us. The question still remains that canconsciousness be really studied as a rigorous scientific discipline? It is indeed true that the study ofconsciousness has been now open to various scientific disciplines mostly within the last twenty to thirtyyears. This has been the case because of the rise of disciplines like neurobiology, cognitive science andeven evolutionary biology. Rigorous scientific disciplines have now started considering studies relating toconsciousness as not only important but rather imperative towards understanding the brain-mindrelationship.In this research paper, I have outlined the main scientific theories that, in my view are studyingconsciousness rigorously. The first broad scientific discipline that studies consciousness is that ofcognitive science and within the broad discipline of cognitive science the main theories are namely, GlobalWorkspace Theory by Bernard Baars, Multiple Drafts Model by Daniel Dennett, Intermediate LevelTheory by Ray Jackendoff and finally Information Integration Theory by GuilioTononi and GeraldEdelman. The second broad discipline that studies consciousness scientifically is that of Neurobiologyand within the discipline of neurobiology, the main theory would that be of finding the neural correlate ofconsciousness as proposed by Christof Koch and Francis Crick. The third discipline would also includethat of evolutionary biology and within that discipline the most recent work is that of Antonio Damasioand more specifically his book titled Self Comes to Mind.